Experimental and Numerical Analysis of the Solar Collector with Stainless Steel Scourers Added to the Absorber Surface - Can, Omer Faruk; Celik, Nevin; Ozgen, Filiz; Kistak, Celal; Taskiran, Ali (Mdpi, 2024)
In this study, a numerical and experimental analysis of a solar collector with roughness elements in the form of stainless-steel scourers on the absorber surface is presented. According to the location type and number of the stainless steel scourers, the absorber surfaces are referred to as the complex surface (C1), less complex surface (C2), and flat surface (C3). A Computational Fluid Dynamics (CFD) analysis was carried out using ANSYS-CFX-R18.2 commercial software. The results were verified with the experimental study. After the numerical study was confirmation with the experimental study, then the detailed investigation was performed by numerical simulations. The extracted results of the numerical and experimental analysis concerned the air temperature and velocity, and thermal efficiency, which varied with respect to the type of collector. As a result, the C1 type yielded the highest air velocity and air temperature, while the lowest values of air velocity and temperature were recorded for the C3 type, according to both the numerical analysis and experimental tests. This trend was similar for the efficiencies. The efficiency was nearly 80% for collectors with stainless-steel scourers, whilst it was 55% for the flat plate collector. The results showed that the experimental and numerical results agreed well.
Keywords: solar collectors; absorber surface; numerical analysis